Wildlife of Bangladesh from Amphibia to Mammalia : a checklist with Bengali names - Khan, Mohammad Ali Reza. (Dhaka : Sahitya Prakash, 2010)
Environment management.
Includes bibliographical references and indexes.
Keywords: Animals -- Bangladesh